2021
DOI: 10.3390/sym13101833
|View full text |Cite
|
Sign up to set email alerts
|

Gliding Down the QCD Transition Line, from Nf = 2 till the Onset of Conformality

Abstract: We review the hot QCD transition with varying number of flavours, from two till the onset of the conformal window. We discuss the universality class for Nf=2, along the critical line for two massless light flavours, and a third flavour whose mass serves as an interpolator between Nf=2 and Nf=3. We identify a possible scaling window for the 3D O(4) universality class transition, and its crossover to a mean field behaviour. We follow the transition from Nf=3 to larger Nf, when it remains of first order, with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…In particular, we detailed the application of our results in finite temperature QCD, where an increasing amount of results coming from recent collision experiments needs to be compared with theoretical predictions, in order to get evidence on the conjectured location of the critical ending point in the (𝑇, 𝜇) phase diagram. The scaling region charting performed here, as well as other new complementary results [11][12][13][14][15], moves in this direction. The goal of constructing a "reference frame" in the neighbourhood of the Ising critical point was efficiently reached using a parametric representation of the model in three dimensions.…”
Section: Discussionsupporting
confidence: 55%
“…In particular, we detailed the application of our results in finite temperature QCD, where an increasing amount of results coming from recent collision experiments needs to be compared with theoretical predictions, in order to get evidence on the conjectured location of the critical ending point in the (𝑇, 𝜇) phase diagram. The scaling region charting performed here, as well as other new complementary results [11][12][13][14][15], moves in this direction. The goal of constructing a "reference frame" in the neighbourhood of the Ising critical point was efficiently reached using a parametric representation of the model in three dimensions.…”
Section: Discussionsupporting
confidence: 55%
“…It is also suggested that the phase transition might stay second-order up to the onset of the conformal window at 9 ≲ N * f ≲ 12. These studies connect naturally to the conformal window of strong interactions [44,45,46], to be further discussed in Section 5.…”
Section: Many Flavor Qcd At Zero µ Bmentioning
confidence: 87%
“…However, its precise value for a larger number of flavours is fairly ambiguous. In the literature, the value varies significantly so there is a large uncertainty associated with the six flavours T c [67][68][69][70][71].…”
Section: Exotic Sectorsmentioning
confidence: 99%